Another Theory of Prostitution - Maria Laura Di Tommaso
This paper presents a model of prostitution as an economic activity characterised by stigma, whose supply is based on the availability of other earning opportunities. On the basis of available empirical evidence and findings from other studies, we put forward a rigorous economic analysis of the industry and its different markets making no restrictive assumptions regarding the gender, pay and nature of forgone earning opportunities of the prostitute, and applying the same behavioural hypotheses to prostitutes and clients.